Graphene Oxide-Catalyzed Subcritical Hydrothermal Liquefaction of Spirulina to Bio-Oil - Chen, Swee Keat (Universiti Teknologi PETRONAS, 2016)
Graphene oxide and graphite oxide were successfully synthesized by oxidizing pure graphite with concentrated sulphuric acid and potassium permanganate using the Hummers’ method. The catalysts were characterized by using Fourier Transform Infrared Spectroscopy. The catalysts were used to catalyse hydrothermal liquefaction of spirulina under subcritical conditions at temperature of 220-300°C. After liquefaction reaction, the yield of bio-oil, solid products, solutes dissolved in aqueous phase and gas products were calculated. Mass balance in terms of mass and mass percent was performed to determine mass of gas products formed during the reaction.